DES meets Gaia: discovery of strongly lensed quasars from a multiplet search. Issue 4 (4th June 2018) - Agnello, A; Lin, H; Kuropatkin, N; Buckley-Geer, E; Anguita, T; Schechter, P L; Morishita, T; Motta, V; Rojas, K; Treu, T; Amara, A; Auger, M W; et al.
ABSTRACT: We report the discovery, spectroscopic confirmation, and first lens models of the first, strongly lensed quasars from a combined search in WISE and Gaia-DR1 over the DES footprint. Their Einstein radii span a range between ≈2.0 arcsec and ≈0.4 arcsec. Two of these (WGD2038-4008, RA = 20:38:02.65, Dec. = −40:08:14.64; WGD2021-4115, RA = 20:21:39.45, Dec. = −41:15:57.11) also have confirmed deflector redshifts. The four-image lens WGD2038-4008, with source and deflector redshifts s = 0.777 ± 0.001 and zl = 0.230 ± 0.002, respectively, has a deflector with radius R eff ≈ 3.4 arcsec, stellar mass (M_/M_)=11.64^+0.20_-0.43, and extended isophotal shape variation. Simple lens models yield Einstein radii R E = (1.30 ± 0.04) arcsec, axis ratio q = 0.75 ± 0.1 (compatible with that of the starlight) and considerable shear-ellipticity degeneracies. The two-image lens WGD2021-4115 has zs = 1.390 ± 0.001 and zl = 0.335 ± 0.002, and Einstein radius R E = (1.1 ± 0.1) arcsec, but higher-resolution imaging is needed to accurately separate the deflector and faint quasar image. Analogous lens model degeneracies hold for the other six lenses (J0146-1133, J0150-4041, J0235-2433, J0245-0556, J0259-2338, and J0508-2748) shown in this paper.